AKTIVITAS SUNSPOT MATAHARI DAN PENGARUHNYA TERHADAP CURAH HUJAN (STUDI KASUS DI PONTIANAK) - Laily Fajarwati; Sigit Nugroho (Unit Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Meteorologi Klimatologi dan Geofisika, 2020)
The climate on earth is strongly influenced by the energy of the sun that reaches earth. The amount of solar radiation which received by the earth is changing based on the rotation of the earth. The sunspot, one of the solar activities, is observed by Balai Pengamatan Antariksa dan Atmosfer Pasuruan. Sunspot is caused by the magnetic activity that inhibited the convection and created the colder temperatures of regions. Sunspots looks like a black spot in the disk of the sun. In addition to solar activity, the Earth's atmosphere is also influenced by the presence of Galactic Cosmic Ray, which is the particles that comes from the outer space and its energy can reach the earth. The number of sunspots (SSN) and Galactic Cosmic Ray (GCR) are two research objects that are related to one another. This research discusses the correlation between SSN and rainfall. The linear regression method which used to test the correlation between the sunspot activity and the rainfall in cycle 24 shows the number of r as 0,037551.